Fibrinolytic system related to pulmonary arterial pressure and lung function of patients with idiopathic pulmonary fibrosis. (14th October 2015) - Ban, Chengjun; Wang, Tongde; Zhang, Shu; Xin, Ping; Liang, Lirong; Wang, Chen; Dai, Huaping
Abstract: Objectives and Aims: To investigate urokinase‐(uPA) and tissue‐type (tPA) plasminogen activator and plasminogen activator inhibitor type‐1 (PAI‐1) levels in patients with idiopathic pulmonary fibrosis (IPF) and to determine the relationship between fibrinolytic system and pulmonary arterial pressure and pulmonary function. Methods: Seventy‐nine patients with IPF were included. Bronchoalveolar lavage fluid (BALF) and blood samples were collected. The concentrations of tPA, uPA and PAI‐1 were measured using enzyme‐linked immunosorbent assay. Doppler echocardiography was used to detect tricuspid regurgitation pressure gradient (TRPG) to estimate pulmonary arterial pressure. Results: BALF tPA elevated ( P  < 0.005), circulatory PAI‐1 decreased ( P  = 0.05) and the ratio of uPA and PAI‐1 decreased ( P  = 0.01) in BALF in IPF patients with pulmonary hypertension (PH) compared to those without PH. Positive linear correlations were found: BALF tPA and TRPG ( r  = 0.558, P  = 0.013); the predicted percentage of diffusion capacity of lung for carbon monoxide adjustments for alveolar volume and BALF uPA ( r  = 0.319, P  = 0.035). Negative linear correlations were as follows: BALF PAI‐1 and the predicted percentage of VCmax ( r  = −0.325, P  = 0.020), or total lung capacity ( r  = −0.312, P  = 0.033); circulatory PAI‐1 and TRPG ( r  = −0.697, P  = 0.003). Conclusions: The change of alveolar fibrolytic system in IPF, especially the uPA reduction and the PAI‐1elevation, contributes to the deterioration of lung function. During the lung injury initiating fibrosis, tPA and PAI‐1 might be leaked out of the pulmonary capillaries into alveoli, resulting in their elevation in alveoli and reduction in circulation, and finally contributing to the development of PH in IPF.